Diretrizes para elaboração de um projeto de impermeabilização aplicado em residência unifamiliar - Bruschi, André Luiz Zarth (2018)
In civil construction all processes that involve a group of activities are minutely characterized for correct execution, usually presented in the form of projects consisting of an execution memorial. Based on these factors, the waterproofing system of the building is neglected when associated to other projects, hardly having a specific project. Waterproofing executed without a project, with materials specified by suppliers and an unskilled labor showed up inefficient and causing pathologies in the structures. The present work developed a waterproofing project of a single-family residence, based on the performance of the humidity in each area, the materials used and the correct execution in stages were specified. In order to collaborate in the realization of a waterproofing project, guidelines were presented for choosing the most appropriate materials and systems, based on specialized bibliographies, technical standards and contact with professionals in the area.